Penerapan Cyber Notary Di Indonesia Dan Kedudukan Hukum Akta Notaris Yang Bebasis Cyber Notary - Mahfuzatun Ni’mah Sona (Officium Notarium, 2022)
Technological developments in the world are increasingly advanced and developing, various technologies have developed that make it easier for people in various ways. One that has an impact on these technological developments is on Notary services, developing electronic-based services or what is called Cyber Notary. However, in Indonesia, the application of Cyber Notary is still very limited, because there is no legal certainty that regulates it. Therefore, this study raises two problem formulations, namely: first, How is the Implementation of Cyber Notary in Indonesia based on the Notary Office Law? and secondly, what is the legal position of a cyber notary-based notary deed? The research method used is normative juridical with literature study using secondary data. The results of the study concluded, First, the application of Cyber Notary in Indonesia has not been fully implemented, because there are still no definite regulations governing the authenticity of deeds made using an electronic system. Second, in the event that the worst possibility occurs where the Notary Deed made electronically will be assumed to be a private Deed, hence this will not become a legal problem as long as the parties do not reject it and Government Agencies should also be able to accept it properly.Key Word: Cyber Notary, Notary Deed, Application. AbstrakPerkembangan teknologi di dunia semakin maju dan berkembang, berbagai teknologi telah berkembang yang memudahkan masyarakat dalam berbagai hal. Salah satu yang terdampak atas perkembangan teknologi tersebut yaitu pada pelayanan Notaris, berkembang pelayanan berbasis elektronik atau yang disebut dengan Cyber Notary. Namun di Indonesia, penerapan Cyber Notary masih sangat terbatas, karena belum ada kepastian hukum yang mengatur tentang hal itu. Oleh karena itu, penelitian ini mengangkat dua rumusan masalah, yaitu : pertama, Bagaimana Penerapan Cyber Notary Di Indonesia berdasarkan Undang-Undang Jabatan Notaris? dan kedua, Bagaimana Kedudukan Hukum Akta Notaris Yang Berbasis Cyber Notary? Metode penelitian yang digunukan adalah yuridis normatif dengan study kepustakaan dengan menggunakan data sekunder. Hasil penelitian menyimpulkan, Pertama, Penerapan Cyber Notary Di Indonesia belum sepenuhnya diterapkan, dikarenakan masih belum adanya peraturan yang pasti yang mengatur terkait dengan keotentikan akta yang dibuat dengan menggunakan sistem elektronik. Kedua, dalam hal terjadi kemungkinan terburuk di mana akta notaris yang dibuat secara elektronik akan diasumsikan menjadi akta dibawah tangan, maka hal tersebut tidak akan menjadi masalah hukum sepanjang para pihak tidak menampiknya, dan seharusnya Instansi Pemerintah juga dapat menerimanya dengan baik.Kata-kata Kunci: Cyber Notary, Akta Notaris, Penerapan.